Structural and Photosensitizing Features of Phthalocyanine—Zeolite Hybrid Nanomaterials1. (17th August 2013) - Grüner, Malte; Siozios, Vassilios; Hagenhoff, Birgit; Breitenstein, Daniel; Strassert, Cristian A.
Abstract: In this work, we have quantified for the first time the fluorescence and singlet oxygen quantum yields of a silicon(IV) phthalocyanine bound to the surface of zeolite L nanocrystals. The photophysical properties were correlated with the absorption spectra and the morphology of the nanoparticles, and most importantly, with the fraction of photoactive chromophores. By comparison with the fluorescence and singlet oxygen quantum yields of the free phthalocyaninate in dilute solution ( Φ F  = 0.50 and Φ ∆  = 0.50, respectively), we conclude that for the most efficient nanoparticles nearly 80% of chromophores are active as monomeric units on the surface, as indicated by the corresponding quantum yields ( Φ F  = 0.40 and Φ ∆  = 0.40). We further functionalized and raised the ζ ‐potential of the best performing nanomaterial to improve its water dispersibility. The functionalization was monitored by thermogravimetric analysis and time‐of‐flight secondary‐ion mass spectrometry, and its influence on the photophysical properties was assessed. The resulting nanomaterials are capable of establishing stable suspensions in water while retaining the ability to form reactive oxygen species upon irradiation with red light. This provides a basis for the rational design of photoactive nanomaterials for photodynamic therapy or water decontamination. Abstract : The linkage of Si(IV) phthalocyanine to the surface of zeolite L nanoparticles enhances its singlet oxygen photosensitizing capability by suppressing the formation of inactive aggregates, even in aqueous environments.